HEALTHCARE SERVICE INNOVATION IN ISOLATED REGIONS: AN ANALYSIS OF THE MOBILE PUSKESMAS PROGRAM IN PAPUA - Ibrahim; Dwijosusilo , Kristyan; Devy Pramudiana, Ika (International Journal of Multidisciplinary Reseach, 2026)
Health service accessibility in isolated areas of Papua represents a critical problem faced by Indonesia, where communities must travel 2-3 days on foot to reach the nearest health facility, resulting in high maternal and infant mortality rates. This study aims to analyze the effectiveness of the Mobile Health Center (Puskesmas Bergerak) Program implementation in Papua in improving access and quality of health services in isolated areas using Everett M. Rogers' diffusion of innovation theory. This research employs a qualitative method with data collection through in-depth interviews with key informants including the Head of Yakonde Village Kurulu District Yahukimo Regency, Head of Wainaga Village, health center staff, and service recipients. Primary data was collected through direct observation and analysis of program evaluation documents to understand the dynamics of health service innovation adoption in isolated areas. Research findings indicate significant success of the Mobile Health Center Program with total elimination of maternal mortality over the past 3 years in Yakonde Village, elimination of infant mortality cases due to diarrhea and high fever, and spontaneous program adoption by neighboring villages through observational learning. This program has successfully transformed health service accessibility from previously unreachable to routine reality with medical team visits every two weeks. The study recommends strengthening the monitoring system, increasing operational budget, developing service protocols adapted to Papua conditions, and establishing local health cadres for program sustainability.